Estimating marine ice thickness beneath the Amery Ice Shelf from airborne radio-echo sounding - Lijuan Wang; Xueyuan Tang; Jingxue Guo; Gang Qiao; Lu An; Lin Li; Jamin S. Greenbaum; Christina Hulbe; Feras A. Habbal; Lenneke M. Jong; Tas van Ommen; Jason L. Roberts; et al. (Journal of Glaciology)
Ice shelves affect the stability of ice sheets by supporting the mass balance of ice upstream of the grounding line. Marine ice, formed from supercooled water freezing at the base of ice shelves, contributes to mass gain and affects ice dynamics. Direct measurements of marine ice thickness are rare due to the challenges of borehole drilling. Here we assume hydrostatic equilibrium to estimate marine ice distribution beneath the Amery Ice Shelf (AIS) using meteoric ice-thickness data obtained from radio-echo sounding collected during the Chinese National Antarctic Research Expedition between 2015 and 2019. This is the first mapping of marine ice beneath the AIS in nearly 20 years. Our new estimates of marine ice along two longitudinal bands beneath the northwest AIS are spatially consistent with earlier work but thicker. We also find a marine ice layer exceeding 30 m of thickness in the central ice shelf and patchy refreezing downstream of the grounding line. Thickness differences from prior results may indicate time-variation in basal melting and freezing patterns driven by polynya activity and coastal water intrusions masses under the ice shelf, highlighting that those changes in ice–ocean interaction are impacting ice-shelf stability.